Rational pharmacotherapy in real clinical practice through the prism of multimorbidity and drug safety - Dmitry I. Trukhan (LLC "MEDIAFORMAT", 2020)
Currently, multimorbidity/comorbidity and drug safety are important components of rational pharmacotherapy in real clinical practice. Cardiovascular diseases occupy a leading place in the structure of non-infectious pathology of the adult population, being the main cause of early disability and premature death. In a review article, using clinical examples, the issues of rational pharmacotherapy in patients with cardiovascular diseases and concomitant comorbid/multimorbid pathology are considered.